Effectiveness of Endoscopic Sinus Surgery for Chronic Rhinosinusitis with Nasal Polyps: Follow-Up on Nasal Obstruction and Recurrence Rates: Nasal Obstruction and Recurrence Rates - Asif, Anam; Mangal, Masoom; Qadir, Muhammad sohail; Aslam, Usman; Khan, Ghulam Dastgir; Afzal, Behram (Pakistan Journal of Health Sciences, 2024)
Chronic rhinosinusitis with nasal polyps is a significant health issue linked with considerable morbidity and reduced life quality. Endoscopic Sinus Surgery (ESS) is a broadly accepted technique for nasal polyp’s treatment. Objective:To assess and compare nasal obstruction in chronic rhinosinusitis patients with nasal polyp’s pre and post-ESS and to evaluate recurrence rates at 3rd and 6th month post-surgery. Methods: The study was conducted as an observational study at Lahore General Hospital ENT Department from June 2019 to June 2020. A total of 88 patients underwent ESS after medical assessment. Nasal obstruction was evaluated using a visual analog scale during follow-up at 2nd week, 3rd month and 6th month. Data were analyzed using SPSS 24.0 with chi-square tests for categorical variables (p<0.05). Results: The mean age of patients was 31.45 ± 11.343 years. At 3rd month post-operative, 59.1% had no nasal obstruction, while 34.1% had mild obstruction. At 6th month, 54.5% had no obstruction, and 37.5% had mild obstruction. Recurrence rates were 25% at 3rd month and 29.5% at 6th month. Conclusions: Higher nasal obstruction and recurrence rates were noted at 6th month compared to 3rd month post-ESS, highlighting the need for long-term follow-up